Identifikasi Jenis-jenis Tumbuhan Mangrove di Pantai Kaili Desa Boyantongo Kecamatan Parigi Selatan - Ningsi, Nur Seftia; Alibasyah, Lestari M.P.; Febriani, Vita Indri; Nurdin, Musdalifah; Buntu, Amalia; Febriawan, Aan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to identify mangrove species occurring in Kaili Beach, Boyantongo Village, South Parigi District. The research employed a descriptive method with a qualitative approach using a field exploration survey. Species identification was conducted based on observations of morphological characteristics, including roots, stems, leaves, flowers, and fruits, supported by measurements of environmental physical parameters such as air temperature (28 °C), salinity (32 ppt), soil pH (7), water pH (6.2), and relative humidity (72% RH). The results revealed that the mangrove vegetation at Kaili Beach comprised five orders, namely Malpighiales, Myrtales, Lamiales, and Sapindales, and four families, including Rhizophoraceae, Lythraceae, Acanthaceae, and Meliaceae. A total of eight mangrove species were identified: Rhizophora apiculata Blume, Rhizophora mucronata Lamk., Ceriops tagal (Perr.) C.B.Rob., Bruguiera gymnorrhiza (L.) Lamk., Sonneratia alba Smith., Avicennia marina (Forsk.) Vierh., Xylocarpus moluccensis Pierre., and Xylocarpus granatum J. Koenig. The presence of these mangrove species indicates that the physical and chemical parameters of Kaili Beach remain within the ecological tolerance range for mangrove growth. However, the slightly acidic water pH (6.2) suggests that habitat conditions are not yet fully optimal.